2000
DOI: 10.1289/ehp.00108955
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of polychlorinated biphenyl-containing and -free transformer fluids on rat testicular steroidogenesis.

Abstract: Polychlorinated biphenyl (PCB)-based transformer fluids belong to a class of environmentally persistent mixtures with known toxic effects. Here, we studied the acute effects of Askarel (which contains Aroclor 1260) and two substitute transformer fluids (the silicone oil-based DC561 and the mineral oil-based ENOL C) on rat testicular steroidogenesis. Single intraperitoneal (ip; 10 mg/kg body weight) or bilateral intratesticular (itt; 25 microg/testis) injections of Askarel markedly decreased serum androgen leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Some PCBs also have been shown to reduce testosterone production, sperm motility and fertilizing capability, as well as alter male accessory structures and inhibit testicular descent in mammals (Andric et al, 2000; Bush et al, 1986; Inglefield and Shafer, 2000). In humans, effects including early menarche, abnormal menstrual cycles, increased incidence of endometriosis, spontaneous abortion, fetal death, premature delivery, and low-weight in offspring have been associated with exposure to PCBs (Cooper et al, 2005; Simmons et al, 2005).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Some PCBs also have been shown to reduce testosterone production, sperm motility and fertilizing capability, as well as alter male accessory structures and inhibit testicular descent in mammals (Andric et al, 2000; Bush et al, 1986; Inglefield and Shafer, 2000). In humans, effects including early menarche, abnormal menstrual cycles, increased incidence of endometriosis, spontaneous abortion, fetal death, premature delivery, and low-weight in offspring have been associated with exposure to PCBs (Cooper et al, 2005; Simmons et al, 2005).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Interestingly, Aroclor enhanced the effect of HDL during the mid-and late-stage of the oestrous cycle. An explanation for this observation is that a single or a number of the PCBs can affect the activity of steroidogenic enzymes (Kannan et al, 1994;Machala et al, 1998;Andric et al, 2000) or to impair lipids metabolism (Bell et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Gavage volume was adjusted according to the weight of each rat. The doses and duration of treatment were selected as per previous publications (Andric et al, ; Andric et al, ; Selvakumar et al, ; Liu et al, ). The control group of animals was maintained and gavaged corn oil vehicle alone.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Aly et al () reported that Arochlor 1254 impaired spermatogenesis as evidenced, at least partly, by induction of oxidative stress in testicular mitochondria. Andric et al () reported that the Aroclor 1260 based‐transformer fluid Askarel inhibits rat testicular steroidogenesis (3βHSD activity) after in vivo and in vitro applications.…”
Section: Introductionmentioning
confidence: 99%